Age-Dependent Behavioral and Metabolic Assessment of AppNL−G−F/NL−G−F Knock-in (KI) Mice - Wang, Shanshan; Ichinomiya, Taiga; Savchenko, Paul; Devulapalli, Swetha; Wang, Dongsheng; Beltz, Gianna; Saito, Takashi; Saido, Takaomi C.; Wagner, Steve L.; Patel, Hemal H.; Head, Brian P. (Frontiers in Molecular Neuroscience, 2022)
Mitochondria play a crucial role in Alzheimer's disease (AD) onset and progression. Traditional transgenic AD mouse models which were widely used in the past decades share a common limitation: the overexpression of APP and overproduction of amyloid-beta (Aß) is accompanied by other APP peptide fragments, which could introduce artificial and non-clinically relevant phenotypes. Here, we performed an in-depth and time-resolved behavioral and metabolic characterization of a clinically relevant AD mouse model engineered to express normal physiological levels of APP harboring humanized Swedish (K670N/M671L), Beyreuther/Iberian (I716F), and Arctic (E693G) mutations, (AppNL-G-F/NL-G-F), termed APP knock-in (APPKI) mice. Our result showed that, APPKI mice exhibited fear learning deficits at 6 m age and contextual memory deficit at 12 m age. Histopathology analysis revealed mild amyloidosis (6E10) accompanied by microgliosis (Iba1) as early as 3 months, which progressed significantly together with significant astrocytosis at 6 and 12 m. We further analyzed hippocampal mitochondrial dysfunction by multiple assays, while 3 m APPKI mice brain mitochondrial function remains similar level as WT mice. Significant mitochondrial dysfunction characterized by decreased ATP production and higher membrane potential with subsequent overproduction of reactive oxygen species (ROS) was observed in mitochondrial isolated from 7 m APPKI mice hippocampus tissue. Morphologically, these mitochondria were larger in volume with decreased level of mitochondrial fusion protein mitofusin-2 (Mfn2). At 12 months, APPKI mice exhibit a significantly decreased total mitochondrial oxygen consumption rate (OCR) in isolated hippocampal mitochondrial detected by high-resolution respirometry. These data indicate early mitochondrial dysfunction in the brain at pre-symptomatic age in the AppNL-G-F/NL-G- mice, which may play a key role in the progression of the disease. Moreover, the identified behavioral and bioenergetic alterations in this clinically relevant AD mouse model provide a valuable tool to optimize the temporal component for therapeutic interventions to treat AD.